THE EFFECT OF WORK ENVIRONMENT, LEADERSHIP STYLE, AND WORKLOAD ON TURNOVER INTENTION FROM THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Yunita Dewi; Siska Yuli Anita; Ghina Ulfa Saefurrohman (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE – Study this analyze influence environment work, style leadership, and burden Work to Turnover intention at PT. JNE in Bandar Lampung. Background This appear Because increased turnover intention due to environment lack of work conducive and burdensome high work, even though some units have apply style good leadership. Research this also aims give understanding about management source Power man in perspective ethics business Islam.METHODOLOGY - Study this use approach quantitative descriptive with sample of 80 selected employees use formula Slovin. Data collected through questionnaire and analysis using SmartPLS through Validity test Reliability as well as testing hypothesis.FINDING – Research result show that environment work influential positive and significant to turnover intention It means the more bad environment Work will the more tall turnover intention. Leadership style influential negative and significant to turnover intention, meaning the more Good style leadership so will the more low turnover intention. Workload influential positive and significant to turnover intention, meaning the more big burden Work so will the more high turnover intention.